INVESTIGATION OF ALKALI PHOSPHATASE ENZYME ACTIVITY OF GAZIANTEP AGRICULTURAL SOILS - Tunç, Erdihan; Könez, Yunus; Çelik, Ömer; Demir, Mustafa (Gaziantep Üniversitesi, 2022)
[Abstract Not Available]
BAPB FEF.YLT.20.06
Keywords: [Keywords Not Available]